What policies do homeowners prefer for building decarbonization and why? An exploration of climate policy support in Canada. (February 2023) - Odland, Severin; Rhodes, Ekaterina; Corbett, Meghan; Pardy, Aaron
Abstract: Public support for home decarbonization policy is required to ensure long-lasting emissions reductions in the buildings sector. While many governments have implemented or announced policies to reduce building GHG emissions, it remains unclear whether these polices receive widespread public support and why. Using survey data from Canadian homeowners (n = 3, 804), we explore (1) levels of homeowner support for specific types of home decarbonization policy in Canada and by Canadian region, (2) individual characteristics associated with support for specific policy types, and (3) heterogeneity across respondents based on patterns of policy support. Results indicate that the majority of homeowners (64–82%) support voluntary policies such as subsidies and loan programs for low-carbon heating technology, while compulsory policies (e.g., carbon taxes, renewable natural gas mandates) receive less support (38–49%). Characteristics associated with consistent support for most home decarbonization policies fall into five categories: altruistic values, climate concern, trust in scientists, positive perceptions of heat pumps, and higher education. Other characteristics are associated with specific policy types. Cluster analysis suggests that respondents fall into three groups: those supportive of all home decarbonization policies (43%), those supportive of voluntary policies only (37%), and those opposed to all home decarbonization policies (20%). Policy implications are discussed. Highlights: Homeowners show high support for subsidies and loans for building decarbonization. Carbon taxes and regulations receive the highest levels of opposition. Five characteristics are associated with consistent support for most home decarbonization policies. Respondents are divided into three clusters based on policy support. Targeted policy proposals may be needed to increase support for compulsory policies.